Photobiomodulation for Oral Mucositis - A Microcosting and Budget Impact Analysis from a Brazilian Perspective - Paula Maria Maracajá Bezerra; Thayana Maria Navarro Ribeiro de Lima; Ana Beatriz Rodrigues Moura; Ana Maria Gondim Valença; Edson Hilan Gomes de Lucena; Yuri Wanderley Cavalcanti; Simone Alves de Sousa (Association of Support to Oral Health Research (APESB), 2023)
Objective: To measure the costs of preventive and therapeutic protocols of Photobiomodulation (PBM) for oral mucositis (OM) and their budgetary impact on Brazil's Ministry of Health (BMH). Material and Methods: A partial economic analysis was performed to estimate the costs using a bottom-up approach from a social perspective. Monetary values were assigned in Brazilian reais (BRL). The costs of the preventive protocol were calculated for five, 30, and 33 consecutive PBM sessions, depending on the antineoplastic treatment instituted. The costs of the therapeutic protocol were calculated for 5 or 10 sessions. The annual financial and budgetary impact was calculated considering the groups of oncologic patients with a higher risk of development of OM, such as those with head and neck and hematological cancer and pediatric patients. Results: The cost of a PBM session was estimated at BRL 23.75. The financial impact of providing one preventive protocol per year for all oncologic patients would be BRL 14,282,680.00, 0.030% of the estimated budget for hospital and outpatient care of the BMH in 2022. The financial and budgetary impacts of providing one treatment for OM for all patients in one year would be BRL 2,225,630.31 (0.005%, most optimistic scenario) and BRL 4,451,355.63 (0.009%, most pessimistic scenario). Conclusion: The budgetary impact of implementing PBM protocols in the Brazilian Healthcare System is small, even in a pessimistic scenario.